Infection of Human Macrophages by Leishmania infantum Is Influenced by Ecto-Nucleotidases - Peres, Nalu Teixeira de Aguiar; Cunha, Luana Celina Seraphim; Barbosa, Meirielly Lima Almeida; Santos, Márcio Bezerra; Oliveira, Fabrícia Alvise de; Jesus, Amélia Maria Ribeiro de; de Almeida, Roque Pacheco (Frontiers in Immunology, 2018)
Ecto-nucleotidase activity is involved in the infection process of Leishmania and various other parasites that enables modulation of host immune responses to promote disease progression. One of the enzymes responsible for this activity is the ecto-nucleoside triphosphate diphosphohydrolase (E-NTPDase). The enzyme hydrolyzes nucleotides tri and/or di-phosphate into monophosphate products, which are subsequently hydrolyzed into adenosine. These nucleotides can serve as purinergic signaling molecules involved in diverse cellular processes that govern immune responses. Given the importance of the extracellular metabolism of these nucleotides during intracellular pathogen infections, this study evaluates the role of ecto-nucleotidase activity during Leishmania infantum (L. infantum) infection in human macrophages. E-NTPDase protein expression and activity was evaluated in L. infantum during purine starvation, adenosine-enriched medium, or in the presence of an inhibitor of ecto-nucleotidases. Results show that E-NTPDase is expressed in L. infantum parasites, including on the cell membrane. Furthermore, functional activity of the enzyme was modulated according to the availability of adenosine in the medium. Purine starvation increased the hydrolytic capacity of nucleotides leading to higher infectivity, while growth in adenosine-enriched medium led to lower infectivity. Moreover, inhibiting E-NTPDase function decreased L. infantum infection in macrophages, suggesting the enzyme may serve as a ligand. Taken together, the ability of L. infantum to hydrolyze nucleotides is directly associated with increased infectivity in macrophages.